Corneal Involvement of Patients with Polymyositis and Dermatomyositis. (2nd January 2020) - Griger, Zoltan; Danko, Katalin; Bodoki, Levente; Aszalos, Zsuzsa; Nemeth, Gabor; Ziad, Hassan; Gesztelyi, Rudolf; Zsuga, Judit; Szodoray, Peter; Kemeny-Beke, Adam
ABSTRACT: Purpose : To evaluate corneal parameters in patients with polymyositis (PM) and dermatomyositis (DM) and compare them with those of healthy controls. Methods : A total of 43 PM and 32 DM patients and 93 controls were enrolled in this cross-sectional, observational, case-control study. Corneal parameters were evaluated by Pentacam. Objective clinical tests of dry eye disease (DED) were also performed. Results : All pachymetric measurements and corneal volumes (CVs) proved to be significantly lower both in PM and DM patients. The values of DM patients were closer to control values than those of the PM patients. For tear break-up time and Schirmer-I test values significant differences were observed between patients and controls, with values decreased both in PM and DM patients. Conclusions : PM patients rather than DM patients tend to develop thinner and low-volume corneas as compared to controls. Additionally, a high prevalence of DED among both PM and DM patients was also detected.